Non-protein-bound iron and 4-hydroxynonenal protein adducts in classic autism - Pecorelli, Alessandra; Leoncini, Silvia; De Felice, Claudio; Signorini, Cinzia; Cerrone, Cosimina; Valacchi, Giuseppe; Ciccoli, Lucia; Hayek, Joussef (Brain & development (Tokyo. 1979), 2013)
A link between oxidative stress and autism spectrum disorders (ASDs) remains controversial with opposing views on its role in the pathogenesis of the disease. We investigated for the first time the levels of non-protein-bound iron (NPBI), a pro-oxidant factor, and 4-hydroxynonenal protein adducts (4-HNE PAs), as a marker of lipid peroxidation-induced protein damage, in classic autism. Patients with classic autism (n=20, mean age 12.0±6.2years) and healthy controls (n=18, mean age 11.7±6.5years) were examined. Intraerythrocyte and plasma NPBI were measured by high performance liquid chromatography (HPLC), and 4-HNE PAs in erythrocyte membranes and plasma were detected by Western blotting. The antioxidant defences were evaluated as erythrocyte glutathione (GSH) levels using a spectrophotometric assay. Intraerythrocyte and plasma NPBI levels were significantly increased (1.98- and 3.56-folds) in autistic patients, as compared to controls (p=0.0019 and p<0.0001, respectively); likewise, 4-HNE PAs were significantly higher in erythrocyte membranes and in plasma (1.58- and 1.6-folds, respectively) from autistic patients than controls (p=0.0043 and p=0.0001, respectively). Erythrocyte GSH was slightly decreased (−10.34%) in patients compared to controls (p=0.0215). Our findings indicate an impairment of the redox status in classic autism patients, with a consequent imbalance between oxidative stress and antioxidant defences. Increased levels of NPBI could contribute to lipid peroxidation and, consequently, to increased plasma and erythrocyte membranes 4-HNE PAs thus amplifying the oxidative damage, potentially contributing to the autistic phenotype.